Characteristics Of Street Children In Cameroon: A Situational Analysis Of Demographic, Socio-Economic And Behavioural Profiles And Challenges - Samuel N. Cumber; Joyce M. Tsoka-Gwegweni (AOSIS, 2016)
Introduction: The issue of street children is one of the global social problems rising in low- and middle-income countries. These children are vulnerable, but because of a lack of sufficient information, it is very difficult for stakeholders to address their plight in Cameroon. Aim: To examine the situation and characteristics of street children in three Cameroonian cities. Objectives: To describe the demographic, socio-economic and behavioural profiles of street children. To identify challenges of street children and to compare the results from the three cities on account of their different settings, cultural history and challenges. Materials and methods: The study was an analytical cross-sectional survey conducted through researcher-administered questionnaires to 399 street children (homeless for at least a month), in three Cameroonian cities from 1 January 2015 to 30 March 2015. Results: The majority of the participants were boys, more than 70% were homeless for less than 12 months and poverty was found to be the most common reason for being on the street. Most of the participants earned less than 500CFA francs (USD 0.85), with many of them resorting to begging, drug abuse, sex work and other risky behaviours. Only two of the respondents (0.5%) regarded the public attitude towards them as supportive. Conclusion: As children roam the streets in search of shelter, food and other basic needs, their future hangs in the balance. Understanding the plight of street children highlights the need for immediate design and implementation of intervention strategies to prevent children from living in the streets and assist those who have become street children.